Schools, Students, and Teachers in Lebanon : Research for Results Program 2021 - World Bank Group; Ministry of Education and Higher Education (World Bank, Washington, DC, 2022)
This report presents the findings from the second phase of the Research for Results (R4R) program. The R4R program is a partnership between the Ministry of Education and Higher Education (MEHE), the World Bank, the UK Foreign, Commonwealth and Development Office, and the United States Agency for International Aid (USAID). The R4R’s primary objective is to generate quantitative evidence on student and teacher performance, school environment and management, and qualitative evidence related to vulnerable youth at risk of dropping out. This evidence-based analysis is supported by policy recommendations and are featured in the new Government five-year general education strategy (2021-2025).